FIGURATIVE LANGUAGE IN RUPERT BROOKE'S POEMS - MUSTAQIM, AMIR (2011)
This research paper is about an analysis of figurative language used in Rupert Brooke's poems. The major problems in this study are to know the kind of figurative language used in Rupert Brooke's poems, to know the meaning of figurative language found in the Rupert Brooke poems and to reveal the dominant figurative language in the Rupert Brooke's poems. The primary sources of data are the research is conducted by using descriptive qualitative method. Researcher uses the primary sources of data are the text of poems itself; A Channel Passage, The Fish, The Great Lover, Heaven, and Menelaus and Helen. The method of the data collection is documentation. Based on the research, the writer concludes that in analyzing literary work, especially for Rupert Brooke's poem, the writer uses a part of whole figures of speech; they are Simile, Metaphor, Personification, Synecdoche, Symbol, Apostrophe, Hyperbole, and Irony. Based on the analysis, the study reveals that there are many meanings and kinds of figurative language in Rupert Brooke's poems. The dominant figurative language that Brooke's used on his poems is personification. Brooke prefers to compare informative statement with giving the attributes of a human being to an animal, an object, or a concept. And his minor figures of speech are Metaphor, Irony, Simile, Apostrophe, Symbol, Hyperbole, and Synecdoche. The meaning revealed from his poem talks about love, faith, and mythology.